Loss, damage and social cohesion: Impacts and next steps for policy and programming - Lily Salloum Lindegaard; Francis Xavier Jarawura (Danish Institute for International Studies (DIIS), 2024)
Climate impacts are intensifying, but knowledge of social impacts is limited. This DIIS Report documents novel findings of considerable social cohesion losses in highly vulnerable areas of the Sahel and West Africa affected by climate change, forced mobility and insecurity. It finds that social cohesion losses are widespread and that these losses have negative material as well as social impacts. Yet the report's assessment of current social cohesion programming shows that focus on climate-related losses to social cohesion is limited. Rather, focus is on areas affected by forced mobility, instability and conflict. Extensive social cohesion losses are therefore likely going overlooked and unaddressed. This report comes at a time of heightened attention to losses and damage, and a move towards dedicated financing and programming. The new Loss and Damage Fund under the United Nations Framework Convention on Climate Change was established at COP27 in 2022 and operationalised at COP28 in 2023 to provide finance to addressing losses and damages. Its board now meets for the first time, moving the fund one step closer to active efforts to address losses and damages in climate vulnerable areas. [...]
Keywords: 300; Ghana; Niger; Niger Red Cross; Danish Red Cross; climate; cohesion; loss and damage